The Influence of Global Muslim Feminism on Indonesian Muslim Feminist Discourse - Nina Nurmila (Al-Jami'ah: Journal of Islamic Studies, 2011)
Since the early 1990s, many Muslim feminist works have been translated into Indonesian. These are, for example, the works of Fatima Mernissi, Riffat Hassan, Amina Wadud, Asghar Ali Engineer, Nawal Saadawi, Asma Barlas and Ziba Mir-Hossaini. These works have been influential in raising the awareness of Indonesian Muslims concerning Islam as a religion which supports equality and justice, but whose message has been blurred by patriarchal interpretations of the Qur’an which mostly put men in the superior position over women. Influenced by Muslim feminists from other countries, there has been an increasing number of Indonesian Muslim scholars, both male and female, who have challenged the existing male biased Qur’anic interpretations on gender relations. These scholars, for instance, are Lily Zakiyah Munir, Nasaruddin Umar, Zaitunah Subhan, Musdah Mulia and Nurjannah Ismail. This paper aims to shed some light on the influence of non-Indonesian Muslim feminist works on Indonesian Muslim feminist discourse. It will also discuss some of the reactions of Indonesian Muslims to the works of Muslim feminists. While some argue for the reinterpretation of the Qur’anic verses from the perspective of gender equality, others feel irritation and anger with the contemporary Muslim feminist critique of the classical Muslim interpretations of the Qur’an, mistakenly assuming that Muslim feminists have criticized or changed the Qur’an. This feeling of anger, according to Asma Barlas, may be caused by the unconscious elevation in the minds of many Muslims of the classical fiqh and tafsir into the position of replacing the Qur’an or even putting these human works above the Qur’an. This, according to her, has unconsciously left the Qur’an “untouchable” (too sacred to be reinterpreted) for most contemporary Muslims.